2006
DOI: 10.1108/13660750610705544
|View full text |Cite
|
Sign up to set email alerts
|

The implications of management by walking about: a case study of a German hospital

Abstract: PurposeThe purpose of this article is to report on case study research conducted in a German hospital and describe the implications that the “Management by walking about” approach had on healthcare employees. “Management by walking about” is widely seen as one of the favoured procedures for increasing employee commitment and shared understanding as well as supporting high trust work relations.Design/methodology/approachThis case study set out to examine the actual labour processes and the concrete experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Our study supports the results of this trial and provides insight into why walkrounds may fail to generate such relationships between senior leaders and front-line staff. Along the same lines, a German study described the potentially counterproductive effects of ‘management by walking around’ on wards and floors due to reinforcement of hierarchical relationships, with leaders asserting managerial control and establishing the expectations, norms and hospital standards during these visits 23. A US study of 30 Veterans Affairs hospitals found that organisations showing characteristics of a hierarchical culture, specifically emphasising rules and control, “may dampen awareness of safety problems and hamper quality improvement efforts by impeding the open flow of information and stifling input from the frontline” 24…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports the results of this trial and provides insight into why walkrounds may fail to generate such relationships between senior leaders and front-line staff. Along the same lines, a German study described the potentially counterproductive effects of ‘management by walking around’ on wards and floors due to reinforcement of hierarchical relationships, with leaders asserting managerial control and establishing the expectations, norms and hospital standards during these visits 23. A US study of 30 Veterans Affairs hospitals found that organisations showing characteristics of a hierarchical culture, specifically emphasising rules and control, “may dampen awareness of safety problems and hamper quality improvement efforts by impeding the open flow of information and stifling input from the frontline” 24…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the study was to examine the impact of implying management by wandering on healthcare employees in one of the German hospitals (Beil-Hildebrand, 2006). Management by wandering was considered as one of the procedures that increase the employees' commitment.…”
Section: Independent Variable (Management By Wandering Around)mentioning
confidence: 99%
“…Including a broader set of perspectives might provide more nuanced results. For example, three studies that use in-depth interviews to explore the impact of safety rounds on frontline staff find that safety rounds negatively impact individuals who participate in the rounds 32 56 57…”
Section: Cautionary Notesmentioning
confidence: 99%
“…Organisations also spend too much time focusing on prioritising problems at the expense of taking action 62. When safety rounds are characterised in these ways, frontline workers become frustrated with them,32 55 feel the programme produces fallible insights55 57 and respond with scepticism and cynicism 56 62…”
Section: Keys To Successful Implementationmentioning
confidence: 99%